Você está na página 1de 10

# MAT 1802 Mathematics for Engineers II

Problem Sheet 2
Solutions

1.

1 0
0 1
cos sin
, A =
and E() =
, show that
If I =
1 0
sin cos
0 1
(a) A2 = I
(b) E() = I cos + A sin
(c) E().E() = E().E()
(d) E(n) = I cos n + A sin n for all n N

Solution:

(b)

cos
E() =
sin

sin cos
=
cos 0

0 0
+
cos sin

sin

1 0
0 1
cos +
sin = I cos + A sin
=
0 1
1 0
(c)

cos
E().E() =
sin

sin cos

cos sin

=
sin cos cos sin

sin

cos

## cos sin + sin cos

=
sin sin + cos cos

cos( + ) sin( + )

sin( + ) cos( + )

(d)

cos
Assume
sin
cos

sin

sin

cos

sin cos k
=
cos sin k

sin k
= E(k).
cos k

k +1

cos
=
sin

sin

cos

cos

sin

## cos k cos sin k sin

=
sin k cos cos sin
cos(k + 1)
=
sin( k + 1)

Then

sin cos k
=
cos sin k

sin k cos

cos k sin

sin

cos

sin( k + 1)
= E((k + 1)).
cos(k + 1)

## Hence result applies for n = k + 1 if it applies for n = k.

We have E() = E(1.). Hence result should apply for n = 2, 3, 4,

1 of 10

2.

Show that 3

Solution: 3

3
0

2
2
2

## 1 commutes with its transpose.

2
2
2
T

0
2

1 = 2

1
2

2
2
2

3 0

2
2 3

1 1 3
3

2
2 . Hence

1 1
3

3 0

2
2 = 3

1 1 3
3

2
2
2

2 0

1 = 2

1 2

2
2
2

2
2

1 1
3

3
6 0 0

2
2 = 0 6 0

0 0 6
1 1

2
2
2

1 =

6 0 0

0 6 0
0 0 6

1
1
1 1

1 i 1 i
3.
Show that A A = 4I where A =
, and A is the complex conjugate of A.
1 1 1 1

1 i 1 i

1
1
1
1 1 1
1
1
1 1
1 1

1 i 1 i
1 i 1 i 1 i 1 i
Solution: A =
. Hence A A =
= 4 I.
1 1 1 1
1 1 1 1 1 1 1 1

1 i 1 i
1 i 1 i 1 i 1 i

4.

Verify thet the following matrices are orthogonal and write down their inverses:

(a)

Solution:

2
1 2

1
2 1 2
3
2 1
2

1 2 2
1
1
(a)
2 1 2
3
3
2 1
2
inverse.

## Sheet 1 Vectors / Solutions

0
1

(b) 0 cos
0 sin

sin
cos

2
1 2
9 0 0 1 0 0

2 1 2 = 0 9 0 = 0 1 0 . Matrix is it own
2 2 1 9 0 0 9 0 0 1

2 of 10

(b)

0
1

0 cos
0 sin

0 1
0

sin 0 cos
cos 0 sin

0
1

Hence 0 cos
0 sin

5.

Evaluate (i)

Solution:

(a)

21

16

17

12

21

16

17

12

(ii)

=4

sin
cos

0 1 0 0

sin = 0 1 0
cos 0 0 1
0
1

= 0 cos
0 sin

97 95

17

=4

23

53

302

176 177

353

76

99 97

21

sin
cos

17

9 16 25 36
16 25 36 49

(iv)

25 36 49 64
36 49 64 81

99 97
97 95

2 97
2 95

= 2

1 97
1 95

= 2(95 97) = 4

## (c) Subtracting C3 from C2 and then adding to C1:

76 23 53
76 76 53
0 76 53
103 199 302 = 103 103 302 = 0 103 302 = 0
176 177

353

9 16 25 36
16 25 36 49
25 36 49 64
36 49 64 81

0 176 353

32

42

52

62

42

52

62

72

52
62

62
72

72
82

82
92

## Subtracting C3 from C4 and C2 from C3 we obtain further

9
16

32

42

52

62

42
52
62

52
62
72

62
72
82

72
=
25 11 13 15
82
2
36 13 15 17
9

7
9

2 2
2 2

25 11 2 2

9
16

7
9

9 11
11 13

= 0.

36 13 2 2
Sheet 1 Vectors / Solutions

3 of 10

6.

Prove that every square matrix can be expressed as the sum of a symmetric matrix and a skew 6 8 5

## symmetric matrix. Express thus the matrix 4 2 3 .

9 7 1

Solution: Let A = [amn] . Let C = [cmn] where cmn = (amn + anm) and let D = dmn = (amn anm).
We observe that cmn = cnm and dmn = dnm. Hence C is a symmetric matrix while D is an
anti-symmetrical matrix. Note also that amn = cmn + dmn . Hence A = C + D as required.
T

6 8 5
6 4 9

4 2 3 = 8 2 7 . Hence C =
9 7 1
5 3 1

6 6 7

6 2 5 and D =
7 5 1

0 2 2

2 0 2 and so
2 2 0

6 8 5 6 6 7 0 2 2

4 2 3 = 6 2 5 + 2 0 2
9 7 1 7 5 1 2 2 0

7.

2 1
5
Evaluate the determinant D = 1 3 2 . Replace each element in D by its cofactor, and
5 2 4
show that the value of the new determinant is D2.

Solution:

2 1
5
1 3 2 = 2(12 4) (4 + 10) + 5(2 15) = 16 14 85 = 83
5 2 4

## Replacing elements by their cofactors we obtain:

8
14 17
D = 14 17
9 = 8(8581) + 14(70 + 153) 17(126 172) = 6889 = (83)2 = D2.
17
9
5

## Sheet 1 Vectors / Solutions

4 of 10

8.

a1
If A1, B1, C1, ... are the cofactors of a1, b1, c1, ... in the determinant = a2

b1
b2

c1
c2 show that A2

a3

b3

c3

A2C3 C2 A3 = b1 .

Solution: A2C3 = (b1c3 b3c1)(a1b2 a2b1) and C2 A3 = (a1b3 a3b1) (b1c2 b2c1)
A2C3 = a1b1b2c3 + a2b1b1c3 + a1b2b3c1 a2b1b3c1
C2 A3 = a1b1b3c2 a1b2b3c1 a3b1b1c2 a3b1b2c1
Hence A2C3 C2 A3 = b1(a1b2c3 a2b1c3 + a2b3c1 a1b3c2 + a3b1c2 + a3b2c1)
= b1{ a1(b2c3 b3c2) b1(a2c3 a3c2) + c1(a2b3 a3b2)} = b1.

9.

(i)

1
Show that = a
a2

1
b
b2

1
c = (b a)(c a)(c b)
c2

a a 2 1 a3

(ii)

## Deduce that b b 2 1 b3 = (1 abc)

c c 2 1 c3

1
a
(iii) By using the result of part (i) evaluate 2
a
a3

1
b
b2
b3

1
c
c2
c3

1
Solution: (i) Subtracting C2 from C3 and C1 from C2, = a
a2
1
= (b a)(c b) a
a2

a a 2 1 a3
a a2
b b 2 1 b3 = b b 2
c c 2 1 c3
c c2

## Sheet 1 Vectors / Solutions

1
b
b2

1
1
c = a
c2
a2

0
ba
b2 a 2

0
cb
c2 b2

0
0
1
1 . Subtracting C2 from C3 we obtain
b+a c+b

1
= (b a)(c b) a
a2

(ii)

1
d
.
d2
d3

0
0
1
0 = (b a)(c b)(c a)
b+a ca
a3 a a 2 1
1 a a2
a a2 1
b3 + b b 2 1 = abc 1 b b 2 + b b 2 1 = (1 abc)
c3
c c2 1
1 c c2
c c2 1

5 of 10

(iii)

1
a
a2
a3

1
b
b2
b3

1
c
c2
c3

1
1
d
a
= 2
2
d
a
3
d
a3

0
ba
b2 a 2
b3 a 3

1
a
= (b a)(c a)(d a) 2
a
a3

0
ca
c2 a2
c3 a 3

0
1
b+a
2
b + ab + a 2

1
= (b a)(c a)(d a)
b+a
b 2 + ab + a 2
1
Note that
b+a
b 2 + ab + a 2

1
c+a
c 2 + ca + a 2

1
1
1
1
= b+a c+a d +a = b
b2
c2
d2
b2
1
a
Hence 2
a
a3

10.

1
b
b2
b3

1
c
c2
c3

1
c
c2

0
d a
d 2 a2
d 3 a3
0
1
c+a
2
c + ca + a 2

1
c+a
c 2 + ca + a 2

0
1
d +a
2
d + ad + a 2

1
d +a
d 2 + da + a 2

1
1
1
1
=
d +a
b+a
c+a
d +a
d 2 + da + a 2
b 2 + a (b + a ) c 2 + a (c + a ) d 2 + a (d + a )
1
1
d + a
d2
b2

1
a
c2

1
a = (c b)(d b)(d c) + 0
d2

1
d
= (b a)(c a)(d a) (c b)(d b)(d c)
d2
d3

a b
c
d
1
a
a +1
a
b
c
a b c d
Factorize: (i) a + 1 1
(ii) a 2
a
b2
c 2 (iii)
a b c d
a
a +1 1
b+c c+a a+b
a b
c d

Solution: (i)

1
a
a +1
1
a
a +1 2
0
2a
1
0
a
a +1 1
a = 1 a a 1 = 1 a a 1 = 2 1 a a 1
a
a +1 1
a a +1 1
a a +1 1
a a +1 1

## Sheet 1 Vectors / Solutions

6 of 10

1
0
a
1 0
a
= 2 0 a 1 = 2 0 a 1 = 2(1 + a3) = 2(1 + a)(1 a + a2)
a a +1 1
a 1
0
a

(ii)

ab

= a b
a
b
c
b+c c+a a+b
ba
2

bc
2

b c
cb
2

1
1
c
= (a b)(b c) a + b b + c c 2
c
a+b
1
1 a + b
c

0
0
a+b+c
0
0
a+b+c
2
= (a b)(b c) a + b b + c
= (a b)(b c) a c b + c
c
c2
1
1
a+b
0
1
a+b
= (a b)(b c)(c a)(a + b + c)

(iii)

1 1 1 1
1 1 1 1
= abcd
= abcd
c d
1 1 1 1
c d
1 1 1 1

a b
c
d
a b c d
a

1 0 0 0
0 1 1 1
= 2abcd
= 2abcd
0 1 1 1
0 1 1 1

2 0 0 0
1 1 1 1
= 2 abcd
1 1 1 1
1 1 1 1

1 0 0
0
0 1 1 1
= 4abcd
0 1 1 1
0 0 0 2

1 0 0 0
0 1 1 0
= 4abcd
= 4abcd
0 1 1 0
0 0 0 1

1 0
0
0 2 0
0 1 1
0 0
0

2
3
(i) 2 x + 3
6 =0
3
4
x+6
x

11.

## Sheet 1 Vectors / Solutions

(ii)

1 0 0
0
1 1 1 1
1 1 1 1
1 1
1 1

1 0 0 0
0 1 1 1
0 1 1 1
0 0 0 1

0
0
= 8abcd
0
1

x+a

x+b

x+c

=0

7 of 10

x
2
Solution: (i) 2 x + 3

3
6 = x{(x +3)(x + 6) 24} 2(2x + 12 18) + 3(8 3x 9)
x+6

## = x3 + 9x2 19x + 9 = (x 1)(x2 + 10x 9) = 0.

x+a
(ii)
c
a

x+a
= c

b
x+b

c
a

x+c

1
b+c
= (x + a + b + c ) 1 x + a + b
1 x+b+c

b+c
x+a+b

c
a

x+b+c

x+c

x+a+b+c
= x+a+b+c

b+c
x+a+b

c
a

x+a+b+c

x+b+c

x+c

0 cax
ca
= (x + a + b + c ) 1 x + a + b
a
x+c
0
ca
x+ca
c
a

0 x
ca
0
0
= (x + a + b + c ) 1 x + b
= (x + a + b+ c) 1 x + b
a
0 x x+ca
0 x
= x2 (x + a + b+ c) = 0

12.

Calculate

Solution:

a 1 1 L 1
1 a 1 L 1

1 1 1 L

a 1 1 L 1
1 a 1 L 1

1 1 1 L

Hence x = 1, 5 34

x
a
x+ca

Hence, x = 0, x = (a + b + c)

1 1 1
1 a 1
= (a n + 1)
M
M
M
M
a
1 1 1

L 1
L 1
O

## (obtained by adding all the rows to R1 and factorised)

1
0
1 a +1
= (a n + 1)
M
M
1 0

0
0
M
0

L
L

0
0
(obtained by subtracting C1 from all columns)
O
M
L a +1

## Sheet 1 Vectors / Solutions

8 of 10

a2
1 + a1
a1
1 + a2

13.

Evaluate

a1
M

a2
M

a1

a2

1 + a3 L
M
O

an
M

L 1 + an

L
L

an
an

1 + a3 L
M
O

an
M

a3
a3

= 1 + ai 1
i =1

a2
M

a1

a2
a3
L 1 + an
1
(obtained by adding all columns to C1)

= 1 + ai 1
i =1

a2
M

L
L

an
an

1 + a3 L

an

a3
a3
M

L
L

an
an

1 + a3 L
M
O

an
M

a2
11
1 1 + a2

a1
M

1 a2
1 1 + a2

a3
a3

a2
M
a2

1 a2
0 1

= 1 + ai 0
i =1

L 1 + an

a3

a3 L an
0 L 0

a2
a3
L 1 + an
0 0 0 L
(obtained by subtracting R1 from all the other rows)

14.

an
an

a3

a2
1 + a1
a1
1 + a2

Solution:

L
L

a3
a3

1 + x2

x
0

1+ x
x

0
M

0
M

x
1 + x2

0
x

L
L

0 = 1 + ai
i =1

1 + x2 L
M
O

x
M

## prove that n n1 = x2 (n1 n2) and hence evaluate n.

1 + x2

1+ x

Solution: n = (1 + x )
2

0
0
M

x
0
M

0
2

x
1+ x
x
M

L x0
0
L
M

1+ x
M

x
x
0 1 + x2

0
x

0
0

1 + x2

1+ x

L
L
L
2

L
O

9 of 10

(n 1) (n 1)

1 + x2

1 + x2
x
x
1 + x2

x
0

= (1 + x )
2

0
M

0
M
x

x
0

1+ x
x

= (1 + x )
2

0
M

(1 + x )
2

1+ x

0
M

0
x

x
M

1+ x
M

0
x
0 1 + x2

(n 1) (n 1)

L
L

1 + x2
L by C2 C1
x
2
x
1+ x L
M

1 + x2

1+ x

Lx

1+ x
M

x
M

0
0

1
0
0
0
2
0 1+ x
x
0
L
2
2
x
1+ x
x
L x 10
0
0
x
1 + x2
L

0
2

0
x

0
M

x
0

x
1 + x2

1+ x

L
L x0
0
L

0
2

0
x

0
M

1 + x2
0

1 + x2
M
O

x
M

1 + x2

L
O

0
M

0
M

L
L

x
1+ x

L
L

x
M

x
1+ x
M

(n 2) (n 2)

L
O

## Hence n = (1 + x2) n1 x2 n2 = x2(n1 n2) + n 1 and result follows.

To find n we proceed as follows:
n
n1
n2
M
4
3

Hence

n1
n2
n3
M
3
2

=
=
=
=
=

x2 n 1
x2 n 2
x2 n3
M
2
x 3
x2 2

x2n2
x2n3
x2n4
M
2
x 2
x 2 1

n 2 = x2 (n 1 1) n = 2 + x2 (n 1 1)

## Since 1 = 1 + x2 and 2 = (1 + x2)2 x2 = 1 + x2 + x4 we obtain

n = x2 n 1 + 1

Note that

3 = x2 2 + 1 = 1 + x2 + x4 + x6.

## This suggests a pattern. We shall prove by induction that

Assume that result applies for n = k:

n = 1 + x2 + x4 + + x2n.

k = 1 + x2 + x4 + + x2k.

Then
k + 1 = x2 k + 1 = 1 + x2 + x4 + + x2k + x2 (k + 1)

Hence if result applies for k it will apply for k + 1. Since the result applies for n = 1, hence by
induction we conclude that it applies for all n. Hence
n = 1 + x2 + x4 + + x2n
Sheet 1 Vectors / Solutions

10 of 10